Hydrocarbon Exports and Economic Growth in Colombia 1960-2016: An Analysis according to the Dutch Disease Hypothesis - Vargas-Restrepo, Johnny Humberto; Saldarriaga-Muñoz, Juan Pablo (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The “Dutch disease” hypothesis predicts that there is a negative relationship between exports of primary goods and the tradable sector of the economy (mainly industry), thus ending up affecting economic growth. This work analyzes this phenomenon in the case of the main Colombian exports, oil and coal. The effect of exports of these fuels on the exchange rate, the tradable sector of the economy and the rate of Colombian economic growth during the period 1960-2016 was modeled using time series, and the results show that this hypothesis is fulfilled. Additionally, it was tested whether the opening processes also caused effects similar to those of the Dutch disease, but no evidence of this was found.